Cultural parallels: India and Iran - Sinha, Atul Kumar (ed.); Singh, Abhay Kumar (ed.) (New Delhi, 2011)
Resemblance creates affinity, but once we probe into the likenesses, the subtle differences in identities stand clarified. True parallels among cultures do not appear by sheer coincidence; they exist more probably due to a common origin, or a similar course of historical development, or like goals, of the analogous cultures. The attempt to seek out the commonalities and features of similitude between two compared civilizations dominates the attention of the historian. But it is a pleasant task to ascertain the 'notes of harmony' and check out the discordant notes from the symphony. On one plane, it generates better social understanding; and on another plane, the realization of common elements in experiences of different peoples, awakens to the laws of eternal truth. The task of the historian that seeking of truth, thus, stands fulfilled with such studies.
Keywords: India-Foreign relations-Iran